2011
DOI: 10.1016/j.jval.2011.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Costo Efectividad de Posaconazol versus Fluconazol/Itraconazol en el Tratamiento Profiláctico de las Infecciones Fúngicas Invasivas en México

Abstract: Posaconazole provides modest incremental benefits compared with standard azole therapy in the prophylaxis against IFIs among high-risk neutropenic patients. Routine Posaconazole use appears a cost saving when the likelihood of IFIs or the cost of treatment medications is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…In the one-way sensitivity analysis, the incremental cost-effectiveness ratio was more sensitive to changes in the costs of IFD; however, the ICER stayed well below the threshold value of €30,000 (€5615.08/LYG), revealing that routine use of posaconazole oral tablets would be a cost-saving prophylactic alternative when the likelihood of IFD or the cost of treatment medications are expected to be particularly high. This result aligned with other similar conclusions in other health care systems [ 41 ]. Posaconazole tablets would lose their dominance if the cost of the management of IFD goes under the €39,750 used in our analysis of the costs of IFD.…”
Section: Discussionsupporting
confidence: 93%
“…In the one-way sensitivity analysis, the incremental cost-effectiveness ratio was more sensitive to changes in the costs of IFD; however, the ICER stayed well below the threshold value of €30,000 (€5615.08/LYG), revealing that routine use of posaconazole oral tablets would be a cost-saving prophylactic alternative when the likelihood of IFD or the cost of treatment medications are expected to be particularly high. This result aligned with other similar conclusions in other health care systems [ 41 ]. Posaconazole tablets would lose their dominance if the cost of the management of IFD goes under the €39,750 used in our analysis of the costs of IFD.…”
Section: Discussionsupporting
confidence: 93%
“…Six economic evaluations of posaconazole were performed using data from a clinical trial of prophylaxis up to 84 days in patients receiving intense chemotherapy for hematological malignancies with clinical endpoints determined at 100 days compared with itraconazole or fluconazole. 13,19,20,21,22,23 The results of these studies all showed that posaconazole was cost saving and was associated with longer life expectancy than standard therapy with either itraconazole or fluconazole. A cost-effectiveness analysis comparing voriconazole with posaconazole prophylaxis, in those undergoing induction with chemotherapy for AML using observational data of a switch from use of voriconazole to posaconazole in a single hospital, showed cost saving and greater therapeutic success with posaconazole.…”
Section: Discussionmentioning
confidence: 97%
“…When the time horizon for the analysis presented in this article was shortened to 6 months, which is similar to the time horizons used in most previously published cost-effectiveness analyses for antifungal prophylaxis with posaconazole, micafungin, or voriconazole in patients with hematological malignancies, 13,19,20,21,22,23,24,26,27 the cost-effectiveness ratios were more favorable for voriconazole because the observed reduction in IFIs was greater between zero and 6 months than between zero and 12 months. In particular, for the AML subpopulation, the cost per IFI avoided was $34,576 at 6 months compared with $66,919 at 12 months.…”
Section: Discussionmentioning
confidence: 99%